The art student's war - Leithauser, Brad (Knopf, 2009)
In his sixth novel, Leithauser has realized a double feat of imagination: a loving historical portrait of a now-vanished Detroit in its heyday, and a keen and affectionate rendering of a young artist, Bianca Paradiso.